The revised patient satisfaction questionnaire (PSQ-R): validity, reliability, equivalence, and network analysis among hospitalized patients in the Chinese population - Zhimin Niu; Lixing Huang; Huanquan He; Songli Mei; Li Li; Mark D. Griffiths (BMC, 2024)
Abstract Objectives The study of comprehensive satisfaction with healthcare is still limited due to nonstandard measurement tools of patient satisfaction for the Chinese population. Therefore, the present study aimed to verify the validity, reliability, and measurement invariance of the revised Patient Satisfaction Questionnaire (PSQ-R) and conducted network analysis among a sample of the Chinese population. Methods A cross-sectional study using telephone surveys was conducted from April 2022 to August 2022. A total of 1377 participants who had been hospitalized completed the survey (481 males [34.9%], mean age = 49.4 years [SD ± 19.0]). Results Four factors ('satisfaction with medical staff', 'satisfaction with hospital', 'satisfaction with medical costs', and 'satisfaction with medical insurance premiums'), were verified through confirmatory factor analysis (CFA) and had good equivalence across genders. The 'satisfaction with medical staff' and 'satisfaction with hospital' factors had the strongest edge intensity in the factor-level network. Conclusions The 18-item (four-factor) PSQ-R has good validity, reliability, and measurement invariance. The four dimensions appear to describe patient satisfaction well among the Chinese population who had been hospitalized. To effectively enhance patient satisfaction, the quality of healthcare service and medical staff skills should both be improved, medical insurance premiums should be increased, and medical costs should be decreased.